Photocatalytic film and its preparation method and application

By preparing a wrinkled ZnO film on the substrate of the photocatalytic film and depositing Ag nanoparticles to form an Ag NPs/ZnO film, the existing photocatalytic film has been solved, and efficient and stable pollutant degradation and reusable effects are achieved.

CN116212869BActive Publication Date: 2025-03-14CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211668955.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-03-14
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

The existing photocatalytic films have shortcomings in stability and pollutant degradation rates, and cannot be reused.

Method used

Ag NPs/ZnO photocatalytic film is formed by preparing a wrinkled ZnO film on a glass or silicon wafer substrate and depositing uniformly distributed Ag nanoparticles by photoreduction. This method prepares ZnO film by hydrothermal method, increasing its specific surface area and adhesion, thereby increasing the loading and photocatalytic effect of nano silver particles.

Benefits of technology

The stability and photocatalytic effect of Ag NPs/ZnO film are improved, and the degradation rate of pollutants is significantly improved. At the same time, the film is easy to be recycled and reused, reducing the cost of sewage treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212869B_ABST
    Figure CN116212869B_ABST
Patent Text Reader

Abstract

The present application provides a photocatalytic film and its preparation method and application. The preparation method includes: providing a glass or silicon wafer substrate; preparing an aqueous solution of sodium citrate and urea; adding zinc acetate to the aqueous solution to prepare a mixed solution; immersing the substrate in the mixed solution for hydrothermal reaction to prepare a ZnO precursor film; calcining the ZnO precursor film to prepare a wrinkled ZnO film; soaking the ZnO film in a silver nitrate solution, taking it out after light exposure, and then drying it to prepare an Ag NPs / ZnO film. The present application first prepares a layer of ZnO film on the surface of the substrate by hydrothermal reaction; then immerses the ZnO film in an AgNO3 solution, and uniformly deposits nanosilver particles (Ag NPs) on the surface of the ZnO film by photoreduction to improve the stability and photocatalytic performance of the Ag NPs / ZnO film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photocatalytic technology, and in particular to a photocatalytic film and a preparation method and application thereof. Background Art

[0002] The rapid development of modern society and the continuous advancement of industrialization have caused serious damage to the ecological environment, which has had an indirect or direct impact on human health. Among them, water pollution is particularly serious. In recent years, the problem of water pollution has become a hot topic for researchers; among them, energy-saving and efficient treatment of sewage is an important aspect of solving the problem of water pollution.

[0003] The rapid development of photocatalysis is due to the cleanliness and infinity of sunlight, and has been applied to sewage treatment and self-cleaning glass. At present, the photocatalytic film prepared in the preparation method has the problems of poor stability, low degradation rate of pollutants and non-reusability. Summary of the invention

[0004] The purpose of this application is to provide a photocatalytic film and its preparation method and application, so as to solve the problems of poor stability of the catalytic film and low degradation rate of pollutants. The specific technical solution is as follows:

[0005] The first aspect of the present application provides a method for preparing a photocatalytic film, comprising: providing a glass or silicon wafer substrate; preparing an aqueous solution of sodium citrate and urea; adding zinc acetate to the aqueous solution to prepare a mixed solution; immersing the substrate in the mixed solution for hydrothermal reaction to prepare a ZnO precursor film; calcining the ZnO precursor film to prepare a wrinkled ZnO film; soaking the ZnO film in a silver nitrate solution, irradiating it with light, taking it out, and then washing and drying it to prepare an AgNPs / ZnO film. Wherein, Ag NPs refers to Ag nanoparticles.

[0006] In some embodiments of the present application, the Ag NPs / ZnO film includes a ZnO thin film and Ag nanoparticles loaded on the ZnO thin film; wherein the particle size of the Ag nanoparticles is 20 nm to 200 nm.

[0007] In some embodiments of the present application, the molar ratio of zinc acetate, sodium citrate, deionized water and urea in the mixed solution is 1:(0.1-0.3):(1000-2000):(1-3); and the concentration of the silver nitrate solution is 0.1-0.5 mol / L.

[0008] In some embodiments of the present application, the process includes: conducting a hydrothermal reaction at a temperature of 100-140°C for 4-8 hours; and conducting a calcination at a heating rate of 3-5°C / min, a temperature of 260-380°C, and a time of 2-4 hours.

[0009] In some embodiments of the present application, the method includes: immersing the sample at room temperature for 0.5 to 1 hour; and irradiating the sample with a xenon lamp at a power of 300 to 500 W for 0.5 to 2 hours.

[0010] In some embodiments of the present application, the substrate is further cleaned before use, and the specific steps are: the substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes respectively.

[0011] The second aspect of the present application provides a photocatalytic film obtained according to the above-mentioned preparation method.

[0012] The third aspect of the present application provides an application of the above-mentioned photocatalytic film in sewage treatment.

[0013] In some embodiments of the present application, the sewage treatment application includes degrading dyes in sewage; wherein the dye is methylene blue.

[0014] Beneficial effects of the implementation scheme of the present application: The preparation method of the Ag NPs / ZnO photocatalytic film provided in the present application prepares a ZnO precursor film on a substrate by adding sodium citrate during the hydrothermal synthesis process, prepares a wrinkled ZnO film by calcining the ZnO precursor film, and prepares an Ag NPs / ZnO film with uniformly dispersed Ag by immersion reduction of the wrinkled ZnO film to improve the stability of the Ag NPs / ZnO film. The ZnO film prepared by the hydrothermal method in the present application has a wrinkled shape, which can not only increase the specific surface area, but also improve the adhesion between the film and the substrate; the large specific surface area can load more nanosilver particles, which is beneficial to improving the photocatalytic effect of the film.

[0015] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0017] Figure 1This is a scanning electron microscope (SEM) photograph of a ZnO precursor film prepared according to Example 1 of the present application;

[0018] Figure 2a This is a scanning electron microscope (SEM) photograph of the ZnO film prepared according to Example 1 of the present application, with a scale of 3 μm;

[0019] Figure 2b This is a scanning electron microscope (SEM) photograph of the ZnO film prepared according to Example 1 of the present application, with a scale of 400 nm;

[0020] Figure 3a This is a scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared according to Example 1 of the present application, with a scale of 10 μm;

[0021] Figure 3b This is a scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared according to Example 1 of the present application, with a scale of 1 μm;

[0022] Figure 4 This is an X-ray energy dispersive spectrometry (EDS) spectrum of the Ag NPs / ZnO photocatalytic film prepared according to Example 1 of the present application;

[0023] Figure 5 This is a mapping diagram of the Ag NPs / ZnO photocatalytic film prepared according to Example 1 of the present application;

[0024] Figure 6 A scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared according to Example 2 of the present application;

[0025] Figure 7 A scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared according to Example 3 of the present application;

[0026] Figure 8 A scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared according to Example 4 of the present application;

[0027] Fig. 9 A scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared according to Example 5 of the present application;

[0028] Fig.10 This is a scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared according to Example 6 of the present application. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.

[0030] The present application proposes a method for preparing a photocatalytic film, comprising: providing a glass or silicon wafer substrate; preparing an aqueous solution of sodium citrate and urea; adding zinc acetate to the aqueous solution to prepare a mixed solution; immersing the substrate in the mixed solution for a hydrothermal reaction to prepare a ZnO precursor film; calcining the ZnO precursor film to prepare a wrinkled ZnO film; and sequentially immersing the ZnO film in a silver nitrate solution, irradiating it with light, taking it out, and then washing and drying it to prepare an Ag NPs / ZnO film.

[0031] The present application provides a method for preparing an Ag NPs / ZnO photocatalytic film. A ZnO precursor film is prepared on a substrate by adding sodium citrate during hydrothermal synthesis, the ZnO precursor film is calcined to prepare a wrinkled ZnO film, and the wrinkled ZnO film is subjected to immersion reduction to obtain an Ag NPs / ZnO film in which Ag is uniformly dispersed, so as to improve the stability of the Ag NPs / ZnO film. The ZnO film prepared by the hydrothermal method in the present application has a wrinkled shape, which can not only increase the specific surface area, but also improve the adhesion between the film and the substrate; the large specific surface area can load more nanosilver particles, which is beneficial to improving the photocatalytic effect of the film.

[0032] In some embodiments of the present application, the mixing in the step of preparing the wrinkled ZnO film is stirring mixing, which can increase the uniformity of the solution; there is no particular limitation on the drying method, as long as the purpose of the present application can be achieved. For example, it can be dried in an oven at 50 to 80°C for 1 to 3 hours.

[0033] In some embodiments of the present application, in the step of preparing the Ag NPs / ZnO film, there is no particular limitation on the washing and drying methods, as long as the purpose of the present application can be achieved. For example, anhydrous ethanol and water can be used for washing, and the film can be dried at 50-80°C.

[0034] In some embodiments of the present application, the Ag NPs / ZnO film comprises a ZnO film and Ag nanoparticles loaded on the ZnO film; wherein the particle size of the Ag nanoparticles is 20 nm to 200 nm.

[0035] In some embodiments of the present application, the molar ratio of zinc acetate, sodium citrate, deionized water and urea in the above mixed solution is 1: (0.1-0.3): (1000-2000): (1-3); the concentration of the silver nitrate solution is 0.1-0.5 mol / L.

[0036] In some embodiments of the present application, the method comprises: conducting a hydrothermal reaction at a temperature of 100 to 140°C for 4 to 8 hours; and calcining at a heating rate of 3 to 5°C / min, a temperature of 260 to 380°C for 2 to 4 hours. Preferably, the calcination condition is to increase the temperature to 300°C at a rate of 5°C / min and keep the temperature for 2 hours.

[0037] In some embodiments of the present application, the method includes: immersing the sample at room temperature for 0.5 to 1 hour; and irradiating the sample with a xenon lamp at a power of 300 to 500 W for 0.5 to 2 hours.

[0038] In some embodiments of the present application, the substrate is further cleaned before use, specifically by ultrasonic cleaning the substrate with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes. The present application also provides a photocatalytic film obtained according to the above preparation method.

[0039] The present application also provides an application of the above-mentioned photocatalytic film in sewage treatment.

[0040] In some embodiments of the present application, the sewage treatment is applied to degrade dyes in sewage; wherein the dye is methylene blue.

[0041] The photocatalytic film provided in the present application has the characteristics of high stability, easy recycling and reuse, and low sewage degradation cost in the application of degrading dyes in sewage.

[0042] Example 1

[0043] <Preparation of Ag NPs / ZnO Photocatalytic Thin Film>

[0044] The glass substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes respectively to obtain a cleaned glass substrate;

[0045] Weigh 6 mmol urea and 0.3 mmol sodium citrate respectively, add them into 70 mL deionized water in turn, stir and mix well to prepare an aqueous solution of sodium citrate and urea;

[0046] Weigh 3 mmol of zinc acetate and add it to an aqueous solution of sodium citrate and urea, stir and mix well to prepare a mixed solution;

[0047] The cleaned glass substrate was immersed in a 100 mL polytetrafluoroethylene autoclave containing the mixed solution prepared above, and the polytetrafluoroethylene autoclave was placed in an oven at 120° C. for 6 hours for hydrothermal reaction, and naturally cooled to room temperature. The substrate was taken out, and washed with water and alcohol for 3 times respectively, and then placed in an oven at 60° C. for drying; preparing a ZnO precursor film;

[0048] The prepared ZnO precursor film was placed in a muffle furnace and calcined at a heating rate of 5°C / min, a temperature of 300°C, and a time of 2h to prepare a wrinkled ZnO film;

[0049] The prepared wrinkled ZnO film was placed in a weighing bottle containing 10 mL of 0.1 mol / L AgNO3 solution and soaked at room temperature for 1 hour. The weighing bottle was then placed under a 300 W xenon lamp for 0.5 hour. Finally, the ZnO film was taken out, washed with water, and dried in an oven at 60°C to obtain the Ag NPs / ZnO photocatalytic film.

[0050] <Morphology Analysis>

[0051] The ZnO precursor film prepared in Example 1 was subjected to morphological analysis. Figure 1 .

[0052] according to Figure 1 As shown in the scanning electron microscope (SEM) photograph of the ZnO precursor film after the hydrothermal reaction prepared in Example 1, the uncalcined ZnO precursor film prepared in Example 1 is continuous and wrinkled on the substrate surface.

[0053] The morphology of the wrinkled ZnO film prepared in Example 1 was analyzed. Figure 2a and Figure 2b .

[0054] according to Figure 2a and Figure 2b As shown in the scanning electron microscope (SEM) photograph of the calcined ZnO film prepared in Example 1, the calcined ZnO film prepared in Example 1 is composed of particles and still maintains a wrinkled shape.

[0055] The Ag NPs / ZnO photocatalytic film prepared in Example 1 was subjected to morphological analysis. Figure 3a , Figure 3b and Figure 4 .

[0056] according to Figure 3a and Figure 3bAs shown in the scanning electron microscope (SEM) photograph of the Ag NPs / ZnO photocatalytic film prepared in Example 1, after photoreduction in Example 1, a large amount of nanosilver particles are uniformly deposited on the surface of the ZnO film, which is conducive to fully exerting the photocatalytic performance of the Ag NPs / ZnO photocatalytic film synthesized in Example 1.

[0057] according to Figure 4 As shown in the X-ray energy dispersive spectrum analysis (EDS) spectrum of the Ag NPs / ZnO photocatalytic film prepared in Example 1, the Ag NPs / ZnO photocatalytic film prepared in Example 1 contains Zn, O and Ag elements, which further verifies that Example 1 prepares a ZnO film and loads Ag NPs on the surface of the glass substrate.

[0058] according to Figure 5 As shown in the Mapping diagram of the Ag NPs / ZnO photocatalytic film prepared in Example 1, the Zn, O and Ag elements are evenly distributed in the Ag NPs / ZnO photocatalytic film prepared in Example 1, indicating that the prepared film material has good uniformity.

[0059] Example 2

[0060] <Preparation of Ag NPs / ZnO Photocatalytic Thin Film>

[0061] The glass substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes respectively to obtain a cleaned glass substrate;

[0062] Weigh 3 mmol urea and 0.3 mmol sodium citrate respectively, add them into 70 mL deionized water in turn, stir and mix well to prepare an aqueous solution of sodium citrate and urea;

[0063] Weigh 3 mmol of zinc acetate and add it to an aqueous solution of sodium citrate and urea, stir and mix well to prepare a mixed solution;

[0064] The cleaned glass substrate was immersed in a 100 mL polytetrafluoroethylene autoclave containing the mixed solution prepared above, and the polytetrafluoroethylene autoclave was placed in an oven at 120° C. for 6 hours for hydrothermal reaction, and naturally cooled to room temperature. The substrate was taken out, and washed with water and alcohol for 3 times respectively, and then placed in an oven at 60° C. for drying; preparing a ZnO precursor film;

[0065] The prepared ZnO precursor film was placed in a muffle furnace and calcined at a heating rate of 5°C / min, a temperature of 300°C, and a time of 2h to prepare a wrinkled ZnO film;

[0066] The prepared wrinkled ZnO film was placed in a weighing bottle containing 10 mL of 0.1 mol / L AgNO3 solution and soaked at room temperature for 1 hour. The weighing bottle was then placed under a 300 W xenon lamp for 0.5 hour. Finally, the ZnO film was taken out, washed with water, and dried in an oven at 60°C to obtain the Ag NPs / ZnO photocatalytic film.

[0067] The Ag NPs / ZnO photocatalytic film prepared in Example 2 was subjected to morphological analysis. Figure 6 .according to Figure 6 As shown in the SEM photo, the wrinkles of the ZnO film in Example 2 are obvious and uniform. After photoreduction, a large amount of silver nanoparticles are uniformly deposited on the surface of the ZnO film.

[0068] Example 3

[0069] <Preparation of Ag NPs / ZnO Photocatalytic Thin Film>

[0070] The glass substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes respectively to obtain a cleaned glass substrate;

[0071] Weigh 6 mmol urea and 0.3 mmol sodium citrate respectively, add them into 70 mL deionized water in turn, stir and mix well to prepare an aqueous solution of sodium citrate and urea;

[0072] Weigh 3 mmol of zinc acetate and add it to an aqueous solution of sodium citrate and urea, stir and mix well to prepare a mixed solution;

[0073] The cleaned glass substrate was immersed in a 100 mL polytetrafluoroethylene autoclave containing the mixed solution prepared above, and the polytetrafluoroethylene autoclave was placed in an oven at 120° C. for 6 hours for hydrothermal reaction, and naturally cooled to room temperature. The substrate was taken out, and washed with water and alcohol for 3 times respectively, and then placed in an oven at 60° C. for drying; preparing a ZnO precursor film;

[0074] The prepared ZnO precursor film was placed in a muffle furnace and calcined at a heating rate of 5°C / min, a temperature of 300°C, and a time of 2h to prepare a wrinkled ZnO film;

[0075] The prepared wrinkled ZnO film was placed in a weighing bottle containing 10 mL of 0.5 mol / L AgNO3 solution and soaked at room temperature for 1 hour. The weighing bottle was then placed under a 300 W xenon lamp for 0.5 hour. Finally, the ZnO film was taken out, washed with water, and dried in an oven at 60°C to obtain the Ag NPs / ZnO photocatalytic film.

[0076] The Ag NPs / ZnO photocatalytic film prepared in Example 3 was subjected to morphological analysis. Figure 7 .according to Figure 7 As shown in the SEM photo, the wrinkles of the ZnO film in Example 3 are obvious and uniform. After photoreduction, a large amount of silver nanoparticles are uniformly deposited on the surface of the ZnO film.

[0077] Example 4

[0078] <Preparation of Ag NPs / ZnO Photocatalytic Thin Film>

[0079] The glass substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes respectively to obtain a cleaned glass substrate;

[0080] Weigh 3 mmol urea and 0.3 mmol sodium citrate respectively, add them into 80 mL deionized water in turn, stir and mix well to prepare an aqueous solution of sodium citrate and urea;

[0081] Weigh 3 mmol of zinc acetate and add it to an aqueous solution of sodium citrate and urea, stir and mix well to prepare a mixed solution;

[0082] The cleaned glass substrate was immersed in a 100 mL polytetrafluoroethylene autoclave containing the mixed solution prepared above, and the polytetrafluoroethylene autoclave was placed in an oven at 120° C. for 6 hours for hydrothermal reaction, and naturally cooled to room temperature. The substrate was taken out, and washed with water and alcohol for 3 times respectively, and then placed in an oven at 60° C. for drying; preparing a ZnO precursor film;

[0083] The prepared ZnO precursor film was placed in a muffle furnace and calcined at a heating rate of 5°C / min, a temperature of 300°C, and a time of 2h to prepare a wrinkled ZnO film;

[0084] The prepared wrinkled ZnO film was placed in a weighing bottle containing 10 mL of 0.1 mol / L AgNO3 solution and soaked at room temperature for 1 hour. The weighing bottle was then irradiated under a 300 W xenon lamp for 0.3 hours. Finally, the ZnO film was taken out, washed with water, and dried in an oven at 60°C to obtain the Ag NPs / ZnO photocatalytic film.

[0085] The Ag NPs / ZnO photocatalytic film prepared in Example 4 was subjected to morphological analysis. Figure 8 .according to Figure 8 As shown in the SEM photo, the wrinkles of the ZnO film in Example 4 are obvious and uniform. After photoreduction, a large amount of silver nanoparticles are uniformly deposited on the surface of the ZnO film.

[0086] Example 5

[0087] <Preparation of Ag NPs / ZnO Photocatalytic Thin Film>

[0088] The glass substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes respectively to obtain a cleaned glass substrate;

[0089] Weigh 6 mmol urea and 0.5 mmol sodium citrate respectively, add them into 80 mL deionized water in turn, stir and mix well to prepare an aqueous solution of sodium citrate and urea;

[0090] Weigh 3 mmol of zinc acetate and add it to an aqueous solution of sodium citrate and urea, stir and mix well to prepare a mixed solution;

[0091] The cleaned glass substrate was immersed in a 100 mL polytetrafluoroethylene autoclave containing the mixed solution prepared above, and the polytetrafluoroethylene autoclave was placed in an oven at 120° C. for 6 hours for hydrothermal reaction, and naturally cooled to room temperature. The substrate was taken out, and washed with water and alcohol for 3 times respectively, and then placed in an oven at 60° C. for drying; preparing a ZnO precursor film;

[0092] The prepared ZnO precursor film was placed in a muffle furnace and calcined at a heating rate of 5°C / min, a temperature of 300°C, and a time of 2h to prepare a wrinkled ZnO film;

[0093] The prepared wrinkled ZnO film was placed in a weighing bottle containing 10 mL of 0.2 mol / L AgNO3 solution and soaked at room temperature for 1 h. The weighing bottle was then placed under a 300 W xenon lamp for 0.3 h. Finally, the ZnO film was taken out, washed with water, and dried in an oven at 60 °C to obtain the Ag NPs / ZnO photocatalytic film.

[0094] The Ag NPs / ZnO photocatalytic film prepared in Example 5 was subjected to morphological analysis. Fig. 9 .according to Fig. 9 As shown in the SEM photo, the wrinkles of the ZnO film in Example 5 are obvious and uniform. After photoreduction, a large amount of silver nanoparticles are uniformly deposited on the surface of the ZnO film.

[0095] Example 6

[0096] <Preparation of Ag NPs / ZnO Photocatalytic Thin Film>

[0097] The glass substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol for 25 to 30 minutes respectively to obtain a cleaned glass substrate;

[0098] Weigh 9 mmol urea and 0.9 mmol sodium citrate respectively, add them to 90 mL deionized water in turn, stir and mix well to prepare an aqueous solution of sodium citrate and urea;

[0099] Weigh 3 mmol of zinc acetate and add it to an aqueous solution of sodium citrate and urea, stir and mix well to prepare a mixed solution;

[0100] The cleaned glass substrate was immersed in a 100 mL polytetrafluoroethylene autoclave containing the mixed solution prepared above, and the polytetrafluoroethylene autoclave was placed in an oven at 120° C. for 6 hours for hydrothermal reaction, and naturally cooled to room temperature. The substrate was taken out, and washed with water and alcohol for 3 times respectively, and then placed in an oven at 60° C. for drying; preparing a ZnO precursor film;

[0101] The prepared ZnO precursor film was placed in a muffle furnace and calcined at a heating rate of 5°C / min, a temperature of 300°C, and a time of 2h to prepare a wrinkled ZnO film;

[0102] The prepared wrinkled ZnO film was placed in a weighing bottle containing 10 mL of 0.4 mol / L AgNO3 solution and soaked at room temperature for 1 hour. The weighing bottle was then placed under a 500 W xenon lamp for 0.3 hours. Finally, the ZnO film was taken out, washed with water, and dried in an oven at 60°C to obtain the Ag NPs / ZnO photocatalytic film.

[0103] The Ag NPs / ZnO photocatalytic film prepared in Example 6 was subjected to morphological analysis. Fig.10 .according to Fig.10 As shown in the SEM photo, the wrinkles of the ZnO film in Example 6 are obvious and uniform. After photoreduction, a large amount of silver nanoparticles are uniformly deposited on the surface of the ZnO film.

[0104] Performance Testing

[0105] <Photocatalytic performance test of photocatalytic film>

[0106] Using a self-made photocatalytic reaction device, 10 cm 2 The Ag NPs / ZnO photocatalytic film prepared in Examples 1 to 6 was added to 50 mL of a methylene blue solution with an initial concentration of 10 mg / L, and stirred in the dark for 30 min to allow the system to reach adsorption equilibrium. Subsequently, a 300 W xenon lamp light source was turned on for a degradation experiment. 2 mL of samples were taken at regular intervals, and the methylene blue concentration in the sample was measured using an ultraviolet spectrophotometer.

[0107] Degradation rate (%) = (initial concentration of methylene blue - concentration of methylene blue after light irradiation) / initial concentration of methylene blue × 100%.

[0108] The performance test results of the Ag NPs / ZnO photocatalytic thin film composite visible light catalysts prepared in Examples 1 to 6 are shown in Table 1.

[0109] Table 1

[0110]

[0111]

[0112] According to the methylene blue degradation rate results of Examples 1 to 6 in Table 1, it can be seen that the Ag NPs / ZnO photocatalytic film prepared by the implementation scheme of the present application has good absorption of visible light, significant photocatalytic effect, and high degradation rate of pollutants.

[0113] In the present application, a layer of wrinkled ZnO film is first prepared on the surface of a glass substrate by a hydrothermal method, and then uniformly distributed Ag nanoparticles are deposited on the surface of the ZnO film by a photoreduction method to obtain an Ag NPs / ZnO photocatalytic film; the prepared AgNPs / ZnO film has good absorption of sunlight, significant and stable photocatalytic effect, and a high degradation rate of pollutants. At the same time, its preparation method is simple, and it is easy to recycle and reuse, with low cost.

[0114] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0115] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0116] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.

Claims

1. A method for preparing a photocatalytic film, characterized in that: include: Providing a glass or silicon wafer substrate; preparing an aqueous solution of sodium citrate and urea; adding zinc acetate to the aqueous solution to prepare a mixed solution; Immersing the substrate in the mixed solution for a hydrothermal reaction to prepare a ZnO precursor film; calcining the ZnO precursor film to prepare a wrinkled ZnO film; The ZnO film is sequentially immersed in a silver nitrate solution, exposed to light, taken out, and then cleaned and dried to prepare an Ag NPs / ZnO film.

2. The preparation method according to claim 1, characterized in that: include: The Ag NPs / ZnO film includes a ZnO film and Ag nanoparticles loaded on the ZnO film; Wherein, the particle size of the Ag nanoparticles is 20nm to 200nm.

3. The preparation method according to claim 1, characterized in that: include: The molar ratio of zinc acetate, sodium citrate, deionized water and urea in the mixed solution is 1:(0.1-0.3):(1000-2000):(1-3); The concentration of the silver nitrate solution is 0.1-0.5 mol / L.

4. The preparation method according to claim 1, characterized in that: include: Carry out a hydrothermal reaction at a temperature of 100 to 140°C for 4 to 8 hours; The calcination is carried out under the conditions of a heating rate of 3 to 5°C / min, a temperature of 260 to 380°C, and a time of 2 to 4 hours.

5. The preparation method according to claim 1, characterized in that: include: Soaking treatment is carried out at room temperature for 0.5 to 1 hour; The illumination is carried out under the conditions that the light source is a xenon lamp, the power is 300-500W, and the time is 0.5-2h.

6. The preparation method according to claim 1, characterized in that: Also includes: The substrate is cleaned before use, and the specific steps are: the substrate is ultrasonically cleaned with concentrated hydrochloric acid, isopropanol, deionized water, and anhydrous ethanol in sequence for 25 to 30 minutes.

7. A photocatalytic film obtained according to the preparation method according to any one of claims 1 to 6.

8. Use of the photocatalytic film according to claim 7 in sewage treatment.

Citation Information

Patent Citations

  • Method for preparing silver deposition modified nano-ZnO thin film

    CN101301609A

  • Preparation method of Ag nanoparticle loaded ZnO film

    CN108003871A